2014
DOI: 10.14218/jcth.2014.00027
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal Bone Marrow-derived Stem Cells Transplantation in Patients with HCV Related Liver Cirrhosis

Abstract: Background and AimsTo evaluate the effect of intraparenchymal transplantation of mesenchymal bone marrow-derived stem cells (BMSCs) in patients with hepatitis C virus (HCV)-related liver cirrhosis (LC).MethodsMononuclear cells were isolated from patient bone marrow and were passaged several times in vitro in order to reach the required volume. Attributes of the BMSCs were evaluated by the presence of the surface markers CD105+, CD90+, and CD73+. Cells from each passage were evaluated for sterility, and they we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…The infection of hepatitis C virus (HCV) can cause liver cirrhosis and degeneration of hepatic tissue. The intraparenchymal transplantation of bone marrow mononuclear cells (BMMNCs) into liver tissue decreases aspartate aminotransferase (AST), alanine transaminase (ALT), bilirubin, CD34, and α -SMA, suggesting that transplanted BMSCs restore hepatic functions through regeneration of hepatic tissues [ 113 ]. In order to meet the growing demand for stem cells transplantation therapy, donor encouragement is always required [ 8 ].…”
Section: Bmscs In Regenerative Medicinementioning
confidence: 99%
“…The infection of hepatitis C virus (HCV) can cause liver cirrhosis and degeneration of hepatic tissue. The intraparenchymal transplantation of bone marrow mononuclear cells (BMMNCs) into liver tissue decreases aspartate aminotransferase (AST), alanine transaminase (ALT), bilirubin, CD34, and α -SMA, suggesting that transplanted BMSCs restore hepatic functions through regeneration of hepatic tissues [ 113 ]. In order to meet the growing demand for stem cells transplantation therapy, donor encouragement is always required [ 8 ].…”
Section: Bmscs In Regenerative Medicinementioning
confidence: 99%
“…In HCV-related liver cirrhosis, autologous BM-MSCs were administered to the liver parenchyma of six patients in a nonrandomized, noncontrolled phase 1 trial (264). MSCs were well tolerated, with jaundice resolving in four of six patients after 6 months and a reduction of transaminitis, although this reduction did not reach statistical significance.…”
Section: Msc Trials In Viral Infectionsmentioning
confidence: 99%
“…When compared to granulocyte-colony-stimulating factor mobilization therapy alone, peripheral blood monocyte transplant therapy offered a significant improvement in liver function as measured by albumin levels and Child-Pugh scores [ 113 ]. Another study found that after intraparenchymal autologous mesenchymal bone marrow-derived stem cell transplantation in hepatitis C patients, the liver showed structural improvement as evidenced by its decreased extracellular matrix protein count on biopsy [ 114 ]. Hepatitis C patients have also been treated with peripheral injection of autologous MSCs, with MELD score improvement but no change in liver fibrosis or regeneration on histopathological examination at six months post-treatment.…”
Section: Potential Applications Of Stem Cells In Liver Diseasesmentioning
confidence: 99%